Role of Science, technology and innovation for responding to Covid-19 - Panja, Amrita; Choudhury, Sujata Maiti (Asian Journal of Medical Sciences, 2022)
The sudden outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the year 2020, has had an impact on different fields of the human life including health sciences, economics, societies and international relations. Science and technology play a crucial role in fighting this ‘war without smoke’. The enormous power of science to manage the critical situation, arises during a pandemic and reminds us that by promoting scientific cultures we can overcome the situation. We must have faith on science in high regard. Although technology will not be able to restrict the onset of a pandemic; nevertheless, it can assist in dealing the emergency more effectively. During this time of sheer uncertainty and constant anxiety, our preparedness to adopt technology has been our lifeline. Certain applications of innovative approach of science and technology include distance learning, contact tracing applications, contactless online deliveries, dissemination of information, technology- based health services. Covid-19 has proved that technology innovations have been assisting in managing the epidemic in a timely, systematic, and peaceful manner. A moral learnt from the Covid-19 pandemic has been to stay well prepared in advance against any crisis at both an individual and national level. Progression in technology is steadily advancing; it will unquestionably continue to grow exponentially. We have to adapt changes in technology faster and continue to invest in building the technology systems for better awareness.